NeuroSAFE frozen section during robot‐assisted radical prostatectomy: peri‐operative and histopathological outcomes from the NeuroSAFE PROOF feasibility randomized controlled trial. (29th March 2021) - Dinneen, Eoin; Haider, Aiman; Grierson, Jack; Freeman, Alex; Oxley, Jon; Briggs, Tim; Nathan, Senthil; Williams, Norman R.; Brew‐Graves, Chris; Persad, Raj; Aning, Jon; Jameson, Charles; et al.
Abstract : Objectives: To report on the methods, peri‐operative outcomes and histopathological concordance between frozen and final section from the NeuroSAFE PROOF feasibility study (NCT03317990). Patients and Methods: Between May 2018 and March 2019, 49 patients at two UK centres underwent robot‐assisted radical prostatectomy (RARP). Twenty‐five patient were randomized to NeuroSAFE RARP (intervention arm) and 24 to standard RARP (control arm). Frozen section was compared to final paraffin section margin assessment in the 25 patients in the NeuroSAFE arm. Operation timings and complications were collected prospectively in both arms. Results: Fifty neurovascular bundles (NVBs) from 25 patients in the NeuroSAFE arm were analysed. When analysed by each pathological section ( n = 250, average five per side), we noted a sensitivity of 100%, a specificity of 99.2%, and an area under the curve (AUC) of 0.994 (95% confidence interval [CI] 0.985 to 1; P ≤0.001). On an NVB basis ( n = 50), sensitivity was 100%, specificity was 92.7%, and the AUC was 0.963 (95% CI 0.914 to 1; P ≤0.001). NeuroSAFE RARP lasted a mean of 3 h 16 min (knife to skin to off table, 95% CI 3 h 2 min–3 h 30 min) compared to 2 h 4 min (95% CI 2 h 2 min–2 h 25 min; P ≤0.001) for standard RARP. There was no morbidity associated with the additional length of operating time on in the NeuroSAFE arm. Conclusion: This feasibility study demonstrates the safety, reproducibility and excellent histopathological concordance of the NeuroSAFE technique in the NeuroSAFE PROOF trial. Although the technique increases the duration of RARP, this does not cause short‐term harm. Confirmation of feasibility has led to the opening of the fully powered NeuroSAFE PROOF randomized controlled trial, which is currently under way at four sites in the UK.